Virgil and the Augustan reception - Thomas, Richard F., 1950- (Cambridge University Press, 2001)
"This book is an examination of the ideological reception of Virgil at specific moments in the last two millennia. Following Tennyson's evaluation of Virgil - "Thou majestic in thy sadness / at the doubtful doom of human kind"--Richard Thomas first scrutinizes the Virgil tradition for readings that refute contemporary dismissals of the putative post-Vietnam Angst of the so-called "Harvard School," then detects the suppression of such readings in the "Augustan" reception, effected through the lens of Augustus and the European successors of Augustus who constructed Rome's first emperor - and Virgil - for their own political purposes